2007
DOI: 10.1093/occmed/kqm053
|View full text |Cite
|
Sign up to set email alerts
|

Maritime health emergencies

Abstract: Background Commercial ships flying the US flag must conform to Coast Guard standards and have medical care available onboard. Consultation with a physician is required if medication is to be prescribed. AimTo evaluate the epidemiology of medical contacts for US ships at sea. MethodRetrospective analysis of cases where shipboard caregivers made contact with US emergency medicine physicians for advice. ResultsThere were 866 cases and 1720 contacts in 48 consecutive months of study. Eighty-eight per cent of cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 6 publications
2
14
1
Order By: Relevance
“…There is little comparable research regarding the health of US ocean‐going seafarers or mariners on inland or coastal tugs, towing vessels, and barges. While comparable data is limited, it is notable that the data confirmed that medical illnesses were the primary cause of telemedicine consultation, as opposed to injuries, a finding similar to McKay's study of US seafarer telemedicine consultations by another service provider from 2001 to 2005 . The high rate of illness among the population demonstrates that medical illness remains a significant problem in seafarers, consistent with limited prior studies investigating seafarers illnesses .…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…There is little comparable research regarding the health of US ocean‐going seafarers or mariners on inland or coastal tugs, towing vessels, and barges. While comparable data is limited, it is notable that the data confirmed that medical illnesses were the primary cause of telemedicine consultation, as opposed to injuries, a finding similar to McKay's study of US seafarer telemedicine consultations by another service provider from 2001 to 2005 . The high rate of illness among the population demonstrates that medical illness remains a significant problem in seafarers, consistent with limited prior studies investigating seafarers illnesses .…”
Section: Discussionsupporting
confidence: 75%
“…For example, a study of American merchant seafarer mortality patterns identified high rates of respiratory cancer and overall cancer deaths, pointing towards potential occupational and behavioral risks specific to merchant seamen . More recently, telemedicine has expanded medical access to this vulnerable population, and telemedicine datasets have provided key information on seafarer medical incidents in their work environment . While telemedicine access for working seafarers continues to expand, studies of medical events in seafarers remain limited by available data, and to our knowledge only one study has described at‐sea medical conditions occurring on US‐flag vessels .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the primary target audience of medical refresher courses are nautical officers as medical lay-persons on board of merchant vessels. The present as well as recent studies reveal that the predominant medical emergencies were trauma [8,10], most probably as a result of the ship’s movements and of the dangerous working environment, especially on container and general cargo ships, due to handling heavy, partly health-endangering cargo [1]. In the authors’ experience, on the subgroup of container ships, illnesses related to general medicine such as diarrhoea, arterial hypertension, and minor lacerations also occur rather frequently at sea.…”
Section: Discussionsupporting
confidence: 68%
“…In order to give a clearer and more comparable picture of injuries and illnesses of patients, the main diagnostic groups were used [8]. This also allowed for a comparison of the study's findings with similar studies [9][10][11][12][13][14]. However, the ten most common specific diagnoses and subgroups of diseases were given for both seafarers and other patients to draw attention to certain diseases and injuries (Figs.…”
Section: Discussionmentioning
confidence: 99%